Tailoring the Mechanical Performance of Carbon Nanotubes Buckypaper by Aramid Nanofibers towards Robust and Compact Supercapacitor Electrode. (2nd February 2022) - Yin, Qing; Jia, Hongbing; Liu, Guigao; Ji, Qingmin
Abstract: Carbon nanotubes (CNTs) buckypaper has shown extraordinary promise for freestanding supercapacitor electrode, but is usually limited by its extremely poor mechanical performance, which is due to the discrete nature of CNTs and rather low packing density. Meanwhile, manipulating the trade‐off between mechanical and electrochemical properties has not yet been realized for buckypaper electrode. Herein, a major breakthrough in optimizing the trade‐off between mechanical performance and compact capacitive delivery for porous buckypaper electrode is demonstrated by using aramid nanofibers (ANFs). Tailoring the microstructure of buckypaper framework by ANFs achieves 6.5‐ and 24.4‐times improvements in strength and toughness, respectively, without significantly sacrificing the volumetric capacitance (only 15.1% decline). Realizing such optimal integration of mechanical and capacitive properties represents a substantial step towards the practically feasible CNTs‐based structural electrodes. Further loading MnO2 conformal coating enables the freestanding electrode to deliver a superior volumetric capacitance of 155.5 F cm −3 while retaining the robust mechanical performance, which is impossible for conventional buckypaper or CNTs‐based bulk electrodes. The maximized structure‐function relationship achieved in this work validates the feasibility of reinforcing buckypaper electrode by ANFs, which may revolutionize the fabrication of advanced CNTs‐based supercapacitor electrodes, and offer a bright avenue for designing multifunctional structural composites. Abstract : The exclusively structural affinity between aramid nanofibers (ANFs) and carbon nanotubes allows the assembly of a porous yet compact buckypaper‐based electrode. By virtue of favorable interfacial π–π interactions, ANFs tailor the microstructure of buckypaper framework, and manipulate the trade‐off between mechanical and capacitive properties. ANFs‐reinforced buckypaper is demonstrated to have great potential in flexible and compact capacitive energy storage.